WILDERNESS SURVIVAL SKILLS : HOW TO STAY ALIVE IN THE WILD WITH JUST A BLADE & YOUR WITS - Holtzman, Bob (Chartwell Books, 2018)
Wilderness survival skills an outdoor survival guide that utilizes the most popular and versatile tool carried by every hiker, camper, and hunter: the knife.